CATFISH KECIL UNIK, Corydoras sp. UNTUK AKUARIUM, TINGKAH LAKU BIOLOGI DAN REPRODUKSINYA [Unique Small Catfish, Corydoras sp. for Aquarium, Biology and Reproduction Habits] - Darti Satyani (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2005)
Small catfish, Corydoras sp. belongs to family Callichthyidae class Siluridae is very popular among aquarist. This genus consist of many species occurring in South America, but only four have been cultured, C. aeneus, C. paleatus, C.panda and C. sterbai. Beside the small size compare to the other catfishes (maximum 7.5 cm), Corydoras has two rows of hard scales. They are bottom dweller, the optimum temperature 24 - 28℃ (depend on species), pH 7 - 7.5 and hardness about 10℃ dH. It is called “the cleaner aquarium” as they like to clean the wall with their mouth. The reproductive behavior is unique. Before ovulation the female brood stock will attach her mouth to male’s genital called “T position” and will suck the sperm. The sperm will be release pass by intestine together with releasing the eggs, into the “pouch” formed by her pelvic fins. The effective fertilization occurred in the “pouch”. Fertilized eggs will bring to the deposit site, usually in object like plant leaf or rocks which has cleaned by the male. Eggs will be leaved and will hatch there in the optimum water condition.